A Highly Contiguous Genome Assembly of a Polyphagous Predatory Mite Stratiolaelaps scimitus (Womersley) (Acari: Laelapidae). (2nd February 2021) - Yan, Yi; Zhang, Na; Liu, Chenglin; Wu, Xinran; Liu, Kai; Yin, Zhan; Zhou, Xuguo; Xie, Lixia
Abstract: As a polyphagous soil-dwelling predatory mite, Stratiolaelaps scimitus (Womersley) (Acari: Laelapidae), formerly known as Stratiolaelaps miles (Berlese), is native to the Northern hemisphere and preys on soil invertebrates, including fungus gnats, springtails, thrips nymphs, nematodes, and other species of mites. Already mass-produced and commercialized in North America, Europe, Oceania and China, S. scimitus will highly likely be introduced to other countries and regions as a biocontrol agent against edaphic pests in the near future. The introduction, however, can lead to unexpected genetic changes within populations of biological control agents, which might decrease the efficacy of pest management or increase the risks to local environments. To better understand the genetic basis of its biology and behavior, we sequenced and assembled the draft genome of S. scimitus using the PacBio Sequel platform II. We generated ∼150× (64.81 Gb) PacBio long reads with an average read length of 12.60 kb. Reads longer than 5 kb were assembled into contigs, resulting in the final assembly of 158 contigs with an N50 length of 7.66 Mb, and captured 93.1% of the BUSCO (Benchmarking Universal Single-Copy Orthologs) gene set ( n = 1, 066). We identified 16.39% (69.91 Mb) repetitive elements, 1, 686 noncoding RNAs, and 13, 305 protein-coding genes, which represented 95.8% BUSCO completeness. Combining analyses of genome family evolution and function enrichment of gene ontology and pathway, a total of 135 families experienced significant expansions, which were mainly involved in digestion, detoxification, immunity, and venom. Major expansions of the detoxification enzymes, that is, P450s and carboxylesterases, suggest a possible genetic mechanism underlying polyphagy and ecological adaptions. Our high-quality genome assembly and annotation provide new insights on the evolutionary biology, soil ecology, and biological control for predaceous mites.